The Concept of Interest and Riba' in a Just Economy and Society According to Islam - EVIDIAWATY, Evidiawaty (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: Whether bank interest in Islam is considered riba or permissible is still debated. The diverse views of economists and scholars depend on the interpretations of the Qur'an and Sunnah. Some consider bank interest to be usury, while others do not. If the interest contains coercion and illegal levies, it is considered usury. Some are against bank interest for justice and a strong economy, while others believe bank interest can hamper the economy. There is also a view of allowing bank interest if it is used for productive businesses. Economists and banks want to encourage savings so that funds can help borrowers, creating economic growth and prosperity.Methodology:This journal article writing method is based on a literature review by reviewing books, interpretations, and writings on usury, bank interest, debt, and other related matters.Findings:The purpose of this writing is to show how the public can get several perspectives on usury and bank interest from the thoughts of economists and scholars.Implication:These views are then linked to the economic conditions of the Indonesian people, who have not fully embraced Sharia-based economic practices. The hope is that the Indonesian Muslim community can choose a view that is more in line with what they believe in their efforts to obey Allah's commands by staying away from what is prohibited by applying it in the present.